Promoting medical competencies through a didactic tutor qualification programme - a qualitative study based on the CanMEDS Physician Competency Framework - Homberg, Angelika; Hundertmark, Jan; Neumann, Boris; Loukanova, Svetla (BMC medical education, 2019)
In peer-led tutorial courses, qualified medical students (“tutors”) provide their peers with opportunities to deepen their theoretical knowledge effectively and to practice clinical skills already in preclinical semesters. At the Medical Faculty of Heidelberg University, a structured medical didactic qualification programme prepares and trains future tutors for their responsibilities. This programme consists of four modules: 1. medical didactics and group leadership, 2. subject-specific training, 3. performance of tutorial courses as well as 4. collegial advice and reflection on the tutors’ activities. The aim of this study is to systematically analyse and present the development of role competencies for medical tutors based on the CanMEDS Physician Competency Framework through the didactic qualification programme. We applied a qualitative research approach to detect CanMEDS role competencies acquisition within the tutor qualification programme. The CanMEDS framework describes key competencies, grouped thematically under seven professional roles. Two tutors and three training coordinators independently assigned the individual modules of the tutor qualification programme to the key competencies of the CanMEDS framework. Tutors and training coordinators compared and discussed the allocations within the groups in a consensus finding process. All authors analysed the findings in order to find out the so-called “hidden curriculum”. The views of both groups are presented separately. The training programme promotes the acquisition of competencies in all seven CanMEDS roles. The roles of the scholar and the leader are promoted in all modules. In addition, the first and fourth module focus predominately on the role of the collaborator, the second on the role of the medical expert and communicator, and the fourth on the role of the professional. The systematic analysis through assignment of the CanMEDS roles to the individual modules of the tutor qualification programme documents the comprehensive acquisition of competencies, not only with regard to the tutor activity, but generally with regard to the later role of the physician. The reflection on one’s own competency acquisition can support the promotion of corresponding competencies in the qualification programme and their transfer into the professional practice later.
Gesehen am 22.08.2019